THE FORMATION OF PSYCHOLOGY OF MANAGEMENT IN THE REPUBLIC OF ARMENIA - Lokyan , A. B․; Aghuzumtsyan, R.V. (Modern Psychology, 2018)
The article presents the history of the development of management psychology in the Republic of Armenia. We present chronologically scientific works, research centers, programs that promote the development of management psychology. The article cover the modern issues of management psychology in Armenia, as well as the long-term objectives of development.
Keywords: management psychology; manager; efficiency of activity; development; long-term objectives